2010
DOI: 10.1136/vr.c3095
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of canine parvovirus and coronavirus in dogs presented with severe diarrhoea to PDSA PetAid hospitals

Abstract: Canine parvovirus (CPV) and canine enteric coronavirus (CECoV) are often cited as causes of diarrhoea in dogs. This study aimed to determine the prevalence of CPV and CECoV in dogs presenting with severe diarrhoea to PDSA PetAid hospitals throughout the UK. A total of 355 samples were collected from the PDSA between 2006 and 2008. All samples were tested for CPV using a long range PCR and for CECoV using RT-PCR. The prevalence of CPV was 58 per cent (95 per cent confidence interval [CI] 52 to 63 per cent), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 20 publications
5
32
0
5
Order By: Relevance
“…In non-vaccinated dogs the prevalence was higher in compared with vaccinated one. The finding was agreed with finding of Godsall et al (2010) where unvaccinated puppies aged between six weeks and six months are at greatest risk of developing CPV infection. The higher prevalence of CPV infection in Non-vaccinated dogs in due to Lack of protective immunity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In non-vaccinated dogs the prevalence was higher in compared with vaccinated one. The finding was agreed with finding of Godsall et al (2010) where unvaccinated puppies aged between six weeks and six months are at greatest risk of developing CPV infection. The higher prevalence of CPV infection in Non-vaccinated dogs in due to Lack of protective immunity.…”
Section: Resultssupporting
confidence: 90%
“…The clinical manifestations of CPV infection depends on the age and immune status of the dogs, virulence of the virus, dose of the virus and pre-existing or concurrent parasitic, bacterial or virus infections (McAdaragh et al, 1982) Factors that predispose parvovirus infection in puppies are lack of protective immunity, intestinal parasites, overcrowded, unsanitary, and stressful environmental conditions (Hoskins, 1997). It has been stated that Doberman, Rottweiler and German shepherd (GS) dogs seem to be more susceptible to Parvovirus infection than other breed (Ling et al, 2012) Unvaccinated puppies aged between six weeks and six months are at greatest risk of developing CPV related disease (Godsall et al, 2010) The prevalence of canine parvovirus infection was reported as 77-80.4% in Thailand, 82.9% in Korea and 6% in Lithuania (Grigonis et al, 2002). The outbreak of CPV disease in dogs was also reported in Belgium and France (1977), Thailand, USA(1978), Portugal, Pakistan, Italy, Spain, Germany (Lamm and Rezabek, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CPV-2 is an important cause of severe (and potentially fatal) diarrhea in unvaccinated (or inadequately vaccinated) dogs, 50,51 and given that this virus is an environmentally tolerant pathogen spread through the fecal-oral route, it is of high concern in canine group settings. 39 Consequently, vaccination guidelines 17,24 …”
Section: Vaccinationmentioning
confidence: 99%
“…This may be due to failure of passive transfer of antibodies via colostrum, incomplete or ineffective primary vaccination course, or failure of vaccination to induce immunity because of interference by maternal antibodies . Unvaccinated puppies aged between six weeks and six months are at greatest risk of developing CPV-related disease, and the incidence of disease is also greater in the warmer months of the year (Godsall et al, 2010;Horner, 1983;Smith-Carr et al, 1997). The reported predisposition of certain breeds -including Rottweiler, Doberman pinscher, German shepherd, American pit bull terrier, Labrador retriever, Springer spaniel and Yorkshire terrier (Day, 1999;Glickman et al, 1985;Goddard and Leisewitz, 2010;Godsall et al, 2010;Smith-Carr et al, 1997) -suggests genetic susceptibility to disease.…”
Section: Introductionmentioning
confidence: 99%